2016
DOI: 10.1371/journal.pone.0154150
|View full text |Cite
|
Sign up to set email alerts
|

Play Behavior in Wolves: Using the ‘50:50’ Rule to Test for Egalitarian Play Styles

Abstract: Social play is known as a cooperative interaction between individuals involving multiple mechanisms. However, the extent to which the equality of individuals’ play styles affects the interaction has not been studied in many species. Dyadic play between wolf puppies, as well as between puppies and adults, was studied to investigate both self-handicapping and offensive behaviors to determine the extent to which wolves engage in play styles where one individual does not dominate the play. Our results did not supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
29
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 39 publications
0
29
0
Order By: Relevance
“…All wolves were born in captivity. Dogs observed in 2014 were born at the center, and spent at least four hours per day with a trainer and other puppies (without the mother) (see [29] for additional information). Both species were kept in a similar manner and therefore have the same life experiences in order to compare the two without fundamental differences in ontogeny.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…All wolves were born in captivity. Dogs observed in 2014 were born at the center, and spent at least four hours per day with a trainer and other puppies (without the mother) (see [29] for additional information). Both species were kept in a similar manner and therefore have the same life experiences in order to compare the two without fundamental differences in ontogeny.…”
Section: Methodsmentioning
confidence: 99%
“…One set of wolf puppies was observed in 2009 and one in 2012 [29]. Each pack consisted of six wolf puppies with both kin and non-kin (no more than two individuals from one litter per pack).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further suggestive evidence for the dominance assessment hypothesis is provided by a recent study investigating play behaviour in wolf pups. Essler et al. (2016) found that pups did not adhere to the 50:50 rule, that is, dyads did not alternate in their winning and losing roles during play, but rather an individual was likely to maintain a constant dominant or submissive role during play with a specific partner.…”
mentioning
confidence: 99%
“…While juvenile play has been suggested to aid in the formation of strong social bonds 5,13 that are required for cooperation, it may also serve to ameliorate tensions between competing individuals within a social group 11,[14][15][16] . Additionally, given the similarities observed between juvenile social play and certain adult behaviours (such as fighting and mating), it may provide individuals with an opportunity to practice and develop the skills required to perform these behaviours in a relatively safe environment 17,18 , where social transgressions are quickly forgiven 12 .…”
mentioning
confidence: 99%